STRATEGI PENGELOLAAN BERITA WEBSITE UIN RADEN FATAH PALEMBANG SEBAGAI MEDIA INFORMASI UNIVERSITAS - Erna Rustiana; Hamidah Hamidah; Sumaina Duku (Tabayyun: Journal of Journalism, 2020)
"The strategy of managing the UIN Raden Fatah website news as a university information media. The problem in this thesis is that people want things that are fast paced. Therefore, in adjusting people's behavior, news presentation is increasingly shifting from starting to display content in the form of long form writing, switching to short forms and finally readers are interested in the news delivered so that it attracts readers to visit the UIN Raden Fatah website and provide feedback (clickbait ). The purpose of this research is to find out how the strategy of managing the news website of UIN Raden Fatah Palembang. This research uses a qualitative descriptive approach through a survey of the object under study, in qualitative research which means the researcher himself or with the help of others, data collection tools in the form of interviews, observations, and documentation. Types and sources of qualitative research data were obtained directly from original sources (not through intermediaries). Primary data sources were obtained through depth interviews such as interviewing the head of Public Relations Dra. Elisma Harfiani, MM and several communicants. Secondary data is used as a complement in the study. Determining the news strategy first determines editorial management for the news strategy consisting of two strategic forms including (1) Writing that is emphasized by the editor of www.radenfatah.ac.id, namely procuring long titles that are rich in keywords and dividing news content into several pages, ) The news policy strategy is an effort to maintain media branding to reap as many visitors as possible by developing content in it. The obstacle that occurs in the management of UIN Raden Fatah's website news is the lack of human resources. Keywords: strategy, management, media, news and website